DESIGNING SOFTWARE FOR ANALYSIS OF SALESBY USING STRAIGHT LINES TREND - Yuli Ekawati; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2000)
Usage Trend mathematically straight line, a lot of help in the preparation and calculation of data, such as preparation of the company's sales data, by obtaining particulars and data and information required, number of sales in each year and changes in sales figures obtained to predict the results of which will come with the software.To get a chart of sales data isby using the straight-line Trendby using hands free, semi-average method and the method of least squares.